2013
DOI: 10.1590/s0004-28032013000400011
|View full text |Cite
|
Sign up to set email alerts
|

Decision Tree Construction and Cost-Effectiveness Analysis of Treatment of Ulcerative Colitis With Pentasa®mesalazine 2 G Sachet

Abstract: -Context -Unspecified Ulcerative Rectocolitis is a chronic disease that affects between 0.5 and 24.5/10 5 inhabitants in the world. National and international clinical guidelines recommend the use of aminosalicylates (including mesalazine) as first-line therapy for induction of remission of unspecified ulcerative rectocolitis, and recommend the maintenance of these agents after remission is achieved. However, multiple daily doses required for the maintenance of disease remission compromise compliance with trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
(27 reference statements)
0
6
0
1
Order By: Relevance
“…22 In all cases, these analyses showed that the optimised therapy was the dominant treatment option (lower costs and higher-quality-adjusted life-years). [17][18][19][20][21][22] A further study focused on the costs and health-related quality of life (HRQoL) impacts of active UC and showed that there were high costs of care (direct and indirect) and adverse effects on HRQOL. 35 Combined with the results from our modelling, it would suggest that the optimised treatment pathway is highly likely to be cost-saving and therefore likely to be dominant over the standard treatment pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 In all cases, these analyses showed that the optimised therapy was the dominant treatment option (lower costs and higher-quality-adjusted life-years). [17][18][19][20][21][22] A further study focused on the costs and health-related quality of life (HRQoL) impacts of active UC and showed that there were high costs of care (direct and indirect) and adverse effects on HRQOL. 35 Combined with the results from our modelling, it would suggest that the optimised treatment pathway is highly likely to be cost-saving and therefore likely to be dominant over the standard treatment pathway.…”
Section: Discussionmentioning
confidence: 99%
“…3 During remission of UC on 5-ASA maintenance therapy, an additional optimisation step is to monitor disease activity through objective markers including endoscopic disease activity, imaging modalities including intestinal ultrasound and biomarkers, such as faecal calprotectin (FC) levels which can act as a trigger for 5-ASA dose escalation, when necessary. 10 While there is a strong rationale for optimisation and good supporting evidence for individual aspects of 5-ASA optimisation, [17][18][19][20][21][22] there has been less investigation into the benefits of a fully optimised treatment pathway in mild-to-moderate UC. This study aimed to use published evidence to model the benefits of the dose optimisation strategy in both induction and maintenance of remission in patients with mild-to-moderately active UC.…”
Section: What Are the New Findings?mentioning
confidence: 99%
See 1 more Smart Citation
“…It uses graphical approach to make comparisons of "competing alternatives and assign values to those alternatives by combining uncertainties, costs, and payoffs into specific numerical values" [76]. Similarly, a study presented the cost-effectiveness assessment for the treatment of ulcerative colitis by using decision tree in a clinical trial [78].…”
Section: Categories Of Breast Cancer-related Researchmentioning
confidence: 99%
“…В настоящее время, исследования по сравнительной экономической оценке различных лекарственных форм, дозировок и режимов применения препаратов 5-АСК имеют высокую актуальность. В частности, подобные исследования проводились в США, Японии, Великобритании, Нидерландах, Испании и других странах [4][5][6][7][8][9][10][11][12]. Однако, в РК, ранее подобные исследования не проводились, более того, не обнаружено также исследований по сравнительной клинико-экономической оценке стратегий применения месалазина ММХ и месалазина с времязависимым высвобождением лекарства и зарубежом, которые послужили объектом нашего исследования.…”
Section: Introductionunclassified